Penerapan Permainan Ular Tangga dalam Pembelajaran Keberagaman Budaya di Indonesia pada Siswa Kelas IV MIS Al Hidayah - Rendi Prilandi; Anggili Pratama; Dinda Prati Dina Arsah; Enjel Anatasia Hutabarat; Fajra Lativa Asri; Deva Maria Pangaribuan; Haris Steven Siregar; Sazkyla Nur Efendi (Politeknik Kampar, 2025)
Indonesia is a multicultural country with hundreds of ethnic groups, languages, traditions, and local arts that form the nation's unique cultural identity. However, in the modern era, cultural literacy among the younger generation is declining, as students are often more familiar with popular digital culture than their own traditional heritage. This community service program aims to increase cultural knowledge among fourth-grade students at MIS Al Hidayah through the use of a modified snakes and ladders game. This board game is designed to include questions, information, and challenges related to Indonesia's cultural diversity, such as ethnic groups, dances, regional songs, and regional specialties. This activity involved four groups of students who took turns playing by rolling the dice and moving the pieces on colored squares red squares contained questions that required students to move backward if they could not answer, green squares provided cultural information, yellow squares presented challenges to dance or sing regional songs, and blue squares served as free spaces. The results showed that students were very enthusiastic, more active, and more motivated to participate in learning. Even students who are usually passive become confident when asked to take on challenges in front of their friends. This activity not only increases cultural knowledge but also encourages collaboration, creativity, and appreciation for Indonesia's cultural diversity. Therefore, the cultural snakes and ladders board game can be an innovative and effective learning medium for strengthening cultural literacy in elementary schools.